2016
DOI: 10.18632/oncotarget.8881
|View full text |Cite
|
Sign up to set email alerts
|

Metformin therapy associated with survival benefit in lung cancer patients with diabetes

Abstract: The purpose of this study is to summarize the currently available evidence regarding the concerned issue by performing a comprehensive meta-analysis. Relevant publications reporting the association of metformin use with survival of lung cancer patients with diabetes were electronically searched to identify eligible studies. The meta-analysis was performed with hazard ratios (HRs) and 95% confidence intervals (95% CIs) as effect measures for disease-free survival(DFS) and overall survival(OS) estimates. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 43 publications
3
33
0
1
Order By: Relevance
“…Most patients of esophageal cancer are diagnosed at advanced stages of the disease due to lack of alarming symptoms at an early stage and are thus no longer suitable for curative surgery [15,16]. Moreover, it was reported that about 20% of patients experience a recurrence after curative esophagectomy [4]. Unlike cancers such as breast cancer and colon cancer whose prognoses have been improved significantly during the last several decades, the outcome of ESCC remains largely unchanged with a 5-year survival rate being 15% to 25% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Most patients of esophageal cancer are diagnosed at advanced stages of the disease due to lack of alarming symptoms at an early stage and are thus no longer suitable for curative surgery [15,16]. Moreover, it was reported that about 20% of patients experience a recurrence after curative esophagectomy [4]. Unlike cancers such as breast cancer and colon cancer whose prognoses have been improved significantly during the last several decades, the outcome of ESCC remains largely unchanged with a 5-year survival rate being 15% to 25% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the survival benefits of metformin for patients with advanced NSCLC . A recent study by Medairos et al reported that metformin exposure was associated with improved progression‐free survival for diabetic patients with early stage NSCLC .…”
Section: Discussionmentioning
confidence: 99%
“…However, another meta-analysis including 17 studies showed metformin had no survival benefit when used as an adjuvant with chemo-radiotherapy while it conferred a better survival outcome to lung cancer patients including those on chemotherapy only [62]. These results were replicated in Menamin et al’s study, which assessed lung cancer patient registry between 1998 and 2009, and they found a weak favorable outcome when metformin was on board before or after diagnosis [63].…”
Section: Metformin and Cancersmentioning
confidence: 99%